KONFLIK BAHASA DI BELGIA: UPAYA PENGELOLAAN POTENSI DISINTEGRASI BANGSA - Rizki Damayanti (Jurnal Universitas Paramadina, 2013)
AbstractLanguage is one of the cultural elements that possessed by humans.Language diversity are usually also closely correlated with ethnic diversity.The ability or inability of a nation to manage multi-language condition willcorrelate with the achievement of integration or disintegration in the nation.The following article will begin by discussing the history of the multilanguagecondition in Belgium, followed by an explanation of therelationship between political conflict with the language conflict. In the nextsection, this paper will explain the special efforts pursued by Belgium inpreventing the disintegration of the nation as a result of language conflict.